Developing a framework for the success of international development projects in the Maldives / Mohamed Yamin… [et.al] - Yamin, Mohamad; Abdul-Rahman, Hamzah; Mohammed Alashwal, Ali (Universiti Teknologi MARA Cawangan Sarawak, 2017)
The paper concentrates on International Development (ID) projects implemented in the Maldives, an island nation in the Indian Ocean. Some of the critical issues reported on these projects include failure of contractors and consultants to deliver goods and services, non-compliance issues on financial management / reporting practices, and project delays. The overarching central question guiding the study is “How can project success be achieved in ID projects implemented in the Maldives?” This paper seeks to assess the challenges facing projects, explore the critical success factors, and project success criteria of ID projects in the Maldives. Furthermore, the study will look into developing a framework for the success of ID projects in the Maldives. It is intended to be carried out based on a qualitative case study approach. The study hopes to capture the views of beneficiaries, project teams, and donors, and thus, help resolve the misalignment between theoretical frameworks and practice.